Association of CLDN6 and CLDN10 With Immune Microenvironment in Ovarian Cancer: A Study of the Claudin Family - Gao, Peipei; Peng, Ting; Cao, Canhui; Lin, Shitong; Wu, Ping; Huang, Xiaoyuan; Wei, Juncheng; Xi, Ling; Yang, Qin; Wu, Peng (Frontiers in Genetics, 2021)
Background The claudin family is a group of transmembrane proteins related to tight junctions. While their involvement in cancer has been studied extensively, their relationship with the tumor immune microenvironment remains poorly understood. In this research, we focused on genes related to the prognosis of ovarian cancer and explored their relationship with the tumor immune microenvironment. Methods The cBioPortal for Cancer Genomics database was used to obtain the genetic variation pattern of the claudin family in ovarian cancer. The ONCOMINE and Gene Expression Profiling Interactive Analysis (GEPIA) databases were used to explore the mRNA expression of claudins in cancers. The prognostic potential of these genes was examined via the Kaplan-Meier plotter. The enrichment of immunological signatures was determined by gene set enrichment analysis (GSEA). The correlations between claudins and the tumor immune microenvironment in ovarian cancer were investigated via the Tumor Immune Estimation Resource (TIMER). Results Claudin genes were altered in 363 (62%) of queried patients/samples. Abnormal expression levels of claudins were observed in various cancers. Among them, CLDN3, CLDN4, CLDN6, CLDN10, CLDN15, and CLDN16 were significantly correlated with overall survival in patients with ovarian cancer. GSEA revealed that CLDN6 and CLDN10 were significantly enriched in immunological signatures of B cell, CD4 T cell, and CD8 T cell. Furthermore, CLDN6 and CLDN10 were negatively correlated and positively correlated, respectively, with immune cell infiltration in ovarian cancer. The expression levels of CLDN6 and CLDN10 were also negatively correlated and positively correlated, respectively, with various gene markers of immune cells in ovarian cancer. Thus, CLDN6 and CLDN10 may participate in immune cell infiltration in ovarian cancer, and these mechanisms may be the reason for poor prognosis. Conclusion Our study showed that CLDN6 and CLDN10 were prognostic biomarkers correlated with the immune microenvironment in ovarian cancer. These results reveal new roles for CLDN6 and CLDN10 as potential therapeutic targets in the treatment of ovarian cancer.